ANALYSIS OF Pseudomonas aeruginosa AND Bacillus subtilis BACTERIA GROWTH IN KNO3 FERTILIZER MEDIA AS NITROGEN BIOREMEDIATION AGENT - Hasanah, Afifah Nurazizatul; Radityani, Fitri Afina; Nuryadin, Devi Faustine Elvina; Sipahutar, Yesika; Nadia, Putri; Gracia, Jeaneatte; Oktavia, Sella (Jurnal Harpodon Borneo, 2023)
Increased population growth is the main cause of increased waste in the environment, especially in water. Increased population growth is the main cause of increased waste in the environment, especially in water. Ammonia, nitrite, and nitrate are forms of inorganic nitrogen, which if they exceed water quality standards, can pollute the environment and are toxic to aquatic biota. However, the toxicity of nitrogen compounds in water can be controlled by microorganisms through nitrification and denitrification processes. In this study, two types of bacteria were used as biological agents in the bioremediation process, Pseudomonas aeruginosa and Bacillus subtilis, which grown anaerobically in media that has been added by KNO3 as a pollutant for 8 days. The results obtained showed that B. subtilis survived for 7 days before entering the cell death phase on the 8th day, while Pseudomonas aeruginosa survived for 5 days and entered the cell death phase on the 6th day. Meanwhile, based on its ability to reduce nitrate, B. subtilis can reduce it up to 99.42%, while P. aeruginosa can reduce it up to 98.26% in 8 days.